ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA BERBASIS KESADARAN BUDAYA ALAT MUSIK TRADISIONAL JAWA BARAT PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Riyani; Pidi Mohamad Setiadi; Anggit Merliana (STKIP Subang, 2026)
Social Studies learning on cultural diversity plays an important role in fostering cultural awareness among elementary school students. However, the introduction of local culture, particularly the traditional musical instruments of West Java, has not been optimal due to the dominance of textbook-based instruction and lecture methods, as well as the limited availability of engaging and contextual learning media. This condition results in students having fewer meaningful learning experiences in recognizing and understanding their local culture. This study aims to analyze the need for learning media on cultural diversity materials to foster students’ cultural awareness of West Javanese traditional musical instruments in elementary schools. The study employed a Research and Development (R&D) approach using the 4D model, limited to the define stage. Data were collected through teacher interviews, curriculum analysis, student characteristics analysis, and learning needs analysis. The findings revealed that teachers require learning media capable of presenting cultural materials in a concrete and engaging manner that is aligned with the characteristics of elementary school students at the concrete operational stage. In addition, learning media that integrate local culture, particularly West Javanese traditional musical instruments, remain limited. Based on the needs analysis, game-based learning media were considered appropriate for development as they can provide active and enjoyable learning experiences. Therefore, a snake and ladder learning media based on cultural awareness of West Javanese traditional musical instruments is considered a potential alternative for Social Studies learning that meets the needs of both teachers and students.